Host range restrictions of oncogenes: myc genes transform avian but not mammalian cells and mht/raf genes transform mammalian but not avian cells. - Li, R (1996)
The host range of retroviral oncogenes is naturally limited by the host range of the retroviral vector. The question of whether the transforming host range of retroviral oncogenes is also restricted by the host species has not been directly addressed. Here we have tested in avian and murine host species the transforming host range of two retroviral onc genes, myc of avian carcinoma viruses MH2 and MC29 and mht/raf of avian carcinoma virus MH2 and murine sarcoma virus MSV 3611. Virus vector-mediated host restriction was bypassed by recombining viral oncogenes with retroviral vectors that can readily infect the host to be tested. It was found that, despite high expression, transforming function of retroviral myc genes is restricted to avian cells, and that of retroviral mht/raf genes is restricted to murine cells. Since retroviral oncogenes encode the same proteins as certain cellular genes, termed protooncogenes, our data must also be relevant to the oncogene hypothesis of cancer. According to this hypothesis, cancer is caused by mutation of protooncogenes. Because protooncogenes are conserved in evolution and are presumed to have conserved functions, the oncogene hypothesis assumes no host range restriction of transforming function. For example, mutated human proto-myc is postulated to cause Burkitt lymphoma, because avian retroviruses with myc genes cause cancer in birds. But there is no evidence that known mutated protooncogenes can transform human cells. The findings reported here indicate that host range restriction appears to be one of the reasons (in addition to insufficient transcriptional activation) why known, mutated protooncogenes lack transforming function in human cells.